Fixed point theorem for Nonlinear $θ-φ-$contraction via $w-$distance - Mohamed Rossafi; Abdelkarim Kari (Jurnal Matematika, Statistika dan Komputasi, 2022)
This paper is aimed to the notion of $θ-φ-$contraction defined on a metric space with $w-$distance. Moreover, fixed point theorems are given in this framework. Some illustrative examples are provided to advocate the usability of our results.As an application, we prove the existence and uniqueness of a solution for the nonlinear Fredholm integral equations.